Public policies and open government - Antik, Analía (Universidad Nacional del Litoral, 2016)
In the present work, we ask ourselves about the usefulness of public policy, its measurability and the adequate tools for continuous control of its design and implementation. Based on the Open Government Partnership experience, which was launched by President Obama during his first term of government – and cautioning that the simple use of the website by Public Administrations does not imply compliance with “open government” standards – public policy is defined as the one which tends to solve “relevant public issues”. To this end, the public policy making process consists of the following stages: agenda setting, formulation, adoption, implementation, follow-up and evaluation. Likewise, the attempt is to classify such stages and establish a value system on which public policies need to be legitimized. Finally, it is considered that the issue of public policy should be included in law studies, taking into account the knowledge that public information is a form of infrastructure, at the same level of importance as other infrastructures (water, electricity, roads). If so, the universities could form, jointly with several government levels, a matrix for the generation of public value data, to allow building governmental action systems and processes with social participation and control with the purpose of observing the performance of governmental organs and their officials and to observe how they manage decision-making as well as materials and human resources, to ultimately tend to reduce corruption levels and improve the use of State assets, and also to empower citizens for them to make better decisions, not only at the time of issuing their vote.